Editions of the 1613 Map of the Grand Duchy of Lithuania: Historiographical Aspect - Braziūnienė, Alma (Knygotyra, 2019)
Based on the initiative of Duke Nicolaus Christophorus Radziwill the Orphan (1549–1616), Great Marshal of Lithuania (1579–1586) and Voivode of Vilnius (1604–1616), a map of the Grand Duchy of Lithuania, titled Magni Ducatus Lithuaniae caeterumque regionum illi adiaciencium exacta descriptio…, was printed in 1613 in the printing house of Willem Janszoon (Blaeu), which was famous at that time for the manufacture of globes and wall maps. It was drawn by Hessel Gerritsz (Lat. Gerardus) and prepared by a team of professionals gathered by N. Ch. Radziwill. The written part of the map (which addresses the reader), separately published also in 1613, glued together from three pages, and designated to the buyers of the wall map of the GDL, was prepared by the famous GDL painter Tomasz Makowski (1575–1630). From 1613 to 1631, this map of the GDL functioned only as a wall map. When W. Blaeu began to publish atlases as well, he included the 1613 wall map of the GDL, which was pressed from four copper plates and included a narrow ornamental edging, in his atlas Appendix Theatri A.Ortelii et Atlantis G. Mercatoris. The readers of the atlas could not observe the territory of the GDL in its entirety, as it was depicted in four pages. Thus, already in another edition of the atlas that was published during the same year of 1631, the map of the GDL was changed and its copper plates were reordered: the segment depicting the lower part of the Dnieper was cut away, and the whole ornamental edging of the map was discarded. Two maps then took shape: one of the GDL’s territory, glued together from four disproportionate plates, and one depicting the lower part of the Dnieper, glued together from two plates. Such a large map of the GDL’s territory (73 × 75 cm) was collapsible and would be included in Blaeu’s atlases near a written piece on Lithuania in the editions of 1631, 1634–1649, and even in one that was published in c. 1670. This map, unconventional for usage in atlases (as it was not bound), was replaced in 1649 by another map made on the basis of the original 1613 variant by W. Blaeu’s son, Joan. This particular specimen was a smaller-scale version of the GDL’s map and was oriented toward the west, not the north. However, as Blaeu’s printing house began to include the 1613 map of the GDL in its atlases, this does not mean that it had also stopped publishing it as a wall map – the buyer could have it made in the same printing shop and purchase, for example, a wide ornamental edging as a supplement to their order (e.g., the specimen belonging to the Uppsala University Library). Only two copies of this 1613 wall map of the GDL are extant, and these can be found in the Uppsala University Library and the Herzogin Anna Amalia Library in Weimar. These specimens are unique in that they allow us to see how an authentic 1613 wall map of the GDL looks like, together with T. Makowski’s text about Lithuania, also marked by a 1613 date. Knowing the history of how the copper plates of this map were used, we may state that the Weimar copy is of earlier origin than the one housed in Uppsala (at least by one year within the 1631 period). This article examines the 1613 map of the GDL from the perspective of book science – we provide an analysis of the publications devoted to the 1613 map of the GDL based on the aspect of how it was published. An all-encompassing historiographical study of the 1613 GDL map is not the goal of the present paper. By chronologically analyzing the works of Lithuanian and foreign authors in an historiographical retrospective, it is emphasized how the various authors writing about this map chose to consider its bibliographical information, how did the perspective regarding the structure of this map shift, etc. An historiographical analysis of the publications on the 1613 map of the GDL has demonstrated that the formal aspects of the map’s origins (what kind of copper plates were prepared for the wall map, of what structure was the map used by William Janszoon Blaeu in the atlases of his printing house and how exactly was it used, etc.) are important in attempting to discern how its functioning had developed over the years.
Keywords: historical cartography; map; map editions; the 1613 map of GDL; historiography of a map